1450. Clinical Characteristics of Patients with Community-Acquired Pneumoniae due to Moraxella catarrhalis in Adults: A Retrospective Single-Center Study in Okinawa Miyako Island in Japan. (26th November 2018) - Hirai, Jun; Kinjo, Takeshi; Haranaga, Shusaku; Fujita, Jiro
Abstract: Background: Previous studies reported that Moraxella catarrhalis was one of the main pathogen in community-acquired pneumonia (CAP); however, only a few investigations describing CAP due to M. catarrhalis (MCAP) have been published until now. Therefore, the data regarding clinical features of MCAP is still unknown. Methods: The primary objective of the present study was to determine the clinical characteristics of patients with MCAP. Pneumonia patients aged over 20 hospitalized between April 2014 and March 2018 were enrolled. Differences on patients' background and clinical parameters between MCAP and CAP caused by S. pneumoniae (SCAP) were compared with elucidate the clinical characteristics of MCAP. Patients with bed-ridden status, residents in nursing home, more than two microorganisms were detected from sputum, were excluded. Results: During the study period, 114 MCAP and 107 SCAP were identified. In two groups, general status was mild (score ≤2 was 65.7% vs. 64.4%) according to Japanese pneumonia severity scoring system (A-DROP), and the qSOFA score was also relatively low (score ≤2 was 95.6% vs. 91.5%). Although there was no difference in the ratio of sex in these groups, the age was significantly higher in MCAP cohort (the mean age; 77 vs. 68 years old, P < 0.01). Compared with SCAP, MCAP had significantly higher pulmonary underling diseases such as bronchiectasis ( P < 0.01), asthma ( P < 0.05), interstitial pneumonia ( P < 0.05), and lung cancer ( P < 0.05), home oxygen therapy ( P < 0.01), and systemic disease ( P < 0.05). Diagnostic concordance rate between sputum smear on Gram-stain and bacterial cultivation was lower in MCAP patients (78% vs. 87.8%; P = 0.05). In radiological findings, bronchopneumonia pattern was predominant in MCAP group than PCAP group (95.6% vs. 62.6%; P < 0.01). On the other hand, developing a chill and co-infection with Flu were common in PCAP patients ( P < 0.01). There was no statistical significant difference on length of treatment and hospital stay in two groups ( P = 0.66 and 0.55, respectively). All patients in both groups recovered. Conclusion: In the present study, the characteristics of MCAP were as follows; (i) mainly occurred in elderly patients under pulmonary and systemic diseases, (ii) presented with relatively mild symptoms, (iii) bronchopneumonia pattern was predominant, and (iv) benign prognosis. Disclosures: All authors: No reported disclosures.